Knowledge and Attitude of Hungarian Athletes towards Long-term Sports Injuries - Szabó Tünde; Stocker Miklós; Győrffy Balázs; Nemes András (Sciendo, 2018)
The purpose of this study was to investigate long-term sports injuries, their prevalence, general identification of and consultation about injuries, and the knowledge among Hungarian athletes related to injury prevention. A questionnaire was designed to survey athletes regarding these topics. Olympic medal winners, nationally selected athletes, and amateur athletes were surveyed, and altogether 502 completed questionnaires were obtained. The data was analyzed with the Chi-square test for dichotomous variables and the Kruskal-Wallis H-test for questions with the Likert scale to try the statistical power of the hypotheses. The results of our analysis show that athletes suffer injuries regardless of their level of play, and that athletes regard their sports to be moderately dangerous. Most athletes would compete despite the risk of permanent injury; they compete with injuries mostly of their own volition; and they will risk potential injuries or long-term health damage to gain exceptional outcomes. Success is the first and foremost desire of athletes, and the risk of injuries or even long-term health damage does not play an important role in the value system of Hungarian athletes. Sport managers and officers of sport federations must be made aware that the first line of prevention of sport injuries is comprehensive medical consultation with proper medical coverage.